Determination of magnesium isotopic ratios of biological reference materials via multi‐collector inductively coupled plasma mass spectrometry. (31st March 2021) - Le Goff, Samuel; Albalat, Emmanuelle; Dosseto, Anthony; Godin, Jean‐Philippe; Balter, Vincent
Abstract : Rationale: Despite a wide range of potential applications, magnesium (Mg) isotope composition has been so far sparsely measured in reference materials with a biological matrix, which is important for the quality control of the results. We describe a method enabling the chemical separation of Mg in geological and biological materials and the determination of its stable isotope composition. Methods: Different geological (BHVO‐1, BHVO‐2, BCR‐1, and IAPSO) and biological (SRM‐1577c, BCR‐383, BCR380R, ERM‐CE464, DORM‐2, DORM‐4, TORT‐3, and FBS) reference materials were used to test the performance of a new sample preparation procedure for Mg isotopic analysis. The procedure consisted of a simple three‐stage elution method to separate Mg from the matrix. Mg isotopic analyses were performed in two different laboratories and with three different multi‐collector inductively coupled plasma mass spectrometry instruments. Results: The biological reference materials show a wide range of δ 26 Mg values (relative to DSM3 standard), spanning over 2‰, from 0.52 ± 0.29‰ (2SD, n = 7) in bovine liver (SRM‐1577c) to −1.45 ± 0.20‰ (2SD, n = 5) in tuna fish (ERM‐CE464), with an external precision of 0.03‰ (2SD, n = 85). Conclusions: This study indicates that isotopic measurements of Mg in biological reference materials show good performance, with the results being within the accepted range. We confirmed that δ 26 Mg values in liver are the most positive of all biological materials reported so far.